Sistem Informasi Penjualan Spare Part Sepeda Motor Berbasis Delphi - Nurhadi Surojudin (Teknik Informatika, Universitas Pelita Bangsa, 2021)
Toko Sumber Berkah motor is a company engaged in trading that sells and purchases spareparts motor. The company still uses the system manually in the sale or purchase of goods. Manually executed system will take a long time, and often found weaknesses in the implementation such as less efficient in recording sales and purchases as well as inaccurate reports of sales and purchases presented. Research methods undertaken by researchers on the basis of direct observation to the store in question and interviews to the store to obtain information in need. The increasing demand for motorcycle spareparts makes store owners experiencing difficulty in processing their data. Therefore required a computerized system to overcome the existing problems in order to facilitate the manufacture of invoices and reports of sales and purchases and accelerate the existing work processes at the store Sumber Berkah Motor. Keywords: Customer, Supplier, goods, shop, sales